2014
DOI: 10.1099/jmm.0.076257-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of Pneumocystis jiroveci in human immunodeficiency virus-positive and -negative immunocompromised patients in The Netherlands

Abstract: Pneumocystis jiroveci infections can cause pneumocystis pneumonia (PCP) or lead to colonization without signs of PCP. Over the years, different genotypes of P. jiroveci have been discovered. Genomic typing of P. jiroveci in different subpopulations can contribute to unravelling the pathogenesis, transmission and spread of the different genotypes. In this study, we wanted to determine the distribution of P. jiroveci genotypes in immunocompetent and immunocompromised patients in The Netherlands and determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
0
2
0
3
Order By: Relevance
“…A decreased frequency of DHPS mutations in other countries including Switzerland, Italy, and Portugal has also been observed [15,18,20,22,[55][56][57][58]. Recent studies of DHPS mutations in North and Central Europe have also shown a low prevalence of DHPS mutations related to the scarce use of sulfa drugs [21,[59][60][61][62][63]. Only one study from Denmark of patients with PcP from before 2000 reported a prevalence of DHPS mutants of 20.4% [64].…”
Section: Developed Countriesmentioning
confidence: 99%
“…A decreased frequency of DHPS mutations in other countries including Switzerland, Italy, and Portugal has also been observed [15,18,20,22,[55][56][57][58]. Recent studies of DHPS mutations in North and Central Europe have also shown a low prevalence of DHPS mutations related to the scarce use of sulfa drugs [21,[59][60][61][62][63]. Only one study from Denmark of patients with PcP from before 2000 reported a prevalence of DHPS mutants of 20.4% [64].…”
Section: Developed Countriesmentioning
confidence: 99%
“…In individual patients with persistent PJP despite adequate therapy with cotrimoxazole, search for mutations in the genes for dihydropteroate synthase or dihydrofolate reductase may be justified [134]. However, P. jirovecii genotypes are unlikely to have clinical relevance in most cases [135,136].…”
Section: Treatment Of Pjpmentioning
confidence: 99%
“…15 Metode pemeriksaan lain yang telah dikembangkan lebih dari 2 dekade adalah diagnosis molekular yang berguna untuk mendeteksi dan melakukan karakterisasi deoxyribonucleic acid (DNA). 16 7,16 Analisis ini dilakukan menggunakan metode PCR dan DNA sekuensing. Amplifikasi dilakukan menggunakan primer pAZ102-H dan pAZ102-E dan dilanjutkan sepasang primer pAZ102-X dan pAZ102-Y (Biotech).…”
Section: Pendahuluanunclassified
“…Amplifikasi dilakukan menggunakan primer pAZ102-H dan pAZ102-E dan dilanjutkan sepasang primer pAZ102-X dan pAZ102-Y (Biotech). 16 (Tabel 1). Fragmen DNA kemudian disekuensing menggunakan metode Dye Terminator dengan elektroforesis kapiler.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation